2002
DOI: 10.1159/000058394
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Salivary Flow Rate in Chronic Hemodialysis Patients

Abstract: Background: Reduced salivary flow has been reported in patients undergoing hemodialysis (HD) treatment. Our aim was to investigate the most important factors associated with stimulated salivary flow rate (ssfr) in chronic HD patients. Methods: Fifty HD patients (27 F, 23 M, mean age 46. 7 ± 13.2 years) were divided into two groups according to the duration of HD treatment as those receiving HD therapy less than or equal to (group I) or those more than (group II) 24 months. Fasting blood samples were obtained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 19 publications
4
26
3
3
Order By: Relevance
“…Only 2 patients reach the normal range salivary flow rate of 0.3 ml/min at baseline, with the mean salivary flow rates before acupressure program being 0.10 8 0.09 ml/min. These results indicate that subjects in this study had more hyposalivation than reported in previous studies [4,[26][27] . This may be attributed to the differences in sample inclusion criteria, since all participants in this study had thirst as a symptom.…”
Section: Discussionsupporting
confidence: 64%
“…Only 2 patients reach the normal range salivary flow rate of 0.3 ml/min at baseline, with the mean salivary flow rates before acupressure program being 0.10 8 0.09 ml/min. These results indicate that subjects in this study had more hyposalivation than reported in previous studies [4,[26][27] . This may be attributed to the differences in sample inclusion criteria, since all participants in this study had thirst as a symptom.…”
Section: Discussionsupporting
confidence: 64%
“…Results on SSFR, BC, and pH revealed that the variables at the three sessions of hemodialysis presented no significant difference from the results of healthy subjects. These findings were unexpected as they are in direct contrast with the findings from most studies in the literature [28,29], which have reported a significantly reduced mean salivary flow in uremic patients. According to these authors, the quantitative change in salivary flow is directly associated with uremia involving salivary glands and a lower degree of hydration due to the restriction of fluid ingestion.…”
Section: Discussioncontrasting
confidence: 89%
“…Saliva has a fundamental role in protecting teeth against dental caries, starting by creating a pellicle of salivary proteins that inhibits enamel demineralization [Bullón et al, 1997;van Nieuw Amerongen et al, 2004]. While some reports have suggested that tobacco use leads to a transient decline in the availability of saliva in the mouth [Sreebny et al,1998], other studies have shown that salivary flow actually increases during tobacco use, or had no discernible differences between smokers and nonsmokers [Pangborn and Sharon, 1971;Bayraktar et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva pH changes have also been cited as likely variables modifying caries risk, with reports suggesting that pH transiently increases while smoking, and after smoking decreases; in some cases, it stays at lower levels [Bayraktar et al, 2002]. At least one report has indicated that tobacco users have a diminished buffering capability [Liede et al, 1999], which in turn might support bacterial changes implicated in dental/oral conditions such as increased Lactobacilli [Sirpa et al, 1999] or Candida albicans and Streptococcus mutans [Edgerton et al, 2000;van Nieuw Amerongen et al, 2004] among smokers.…”
Section: Discussionmentioning
confidence: 99%